Home quarantined: Privacy at risk in technologically-oriented learning amidst COVID-19 pandemic - Client William Melchor Malinao; Mark Mata Sotto (Institute of Advanced Engineering and Science, 2022)
The COVID-19 triggers technologically-oriented learning and is critical in ensuring that education continues after schools close physically. The internet has a plethora of learning opportunities but may invite privacy risks to users. Using descriptive-comparative research design, the study determined the contents and artifacts exchanged in online portals, the extent of use of social media sites, teaching-learning platforms, and educational websites. The sample was 341 college students of a family-owned private higher education institution. Finally, the difference in online privacy risk management practices was determined when grouped by selected demographic variables. Using means, t-test, and ANOVA, findings from an online survey showed that personal information is shared the most in online portals. For online learning, students heavily relied on Facebook, Microsoft Teams, and Google. To protect their privacy, respondents from all classes follow online management practices. Generally, the respondents' good affordances and decorum in the online media imply that they have good behavior and value creation. Still, a comprehensive strategy to safeguard data among learners in the utilization of online productivity platforms is a must.